1983
DOI: 10.1139/m83-174
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory activity, molar growth yields, and ATP content in an Arthrobacter sp. ammonium-limited chemostat culture

Abstract: Respiratory activity, molar growth yields, and ATP content in. an Arthrobacter sp. ammonium-limited chemostat culture. Can. J. Microbiol. 29: 11 36-1140.ArthrobacterfIuorescens was grown in chemostat culture under ammonium-limited conditions and respiratory activity; molar growth yields and ATP content were determined over a wide range of dilution rates. Within a range of dilution rates between 0.10 h-' and 0.20 h-', morphological transition occurred, the ratio of cocci to rods appearing inversely related to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

1984
1984
1995
1995

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…2). These results confirmed previous findings (CACCIARI et al 1985) and indicated that the organism grew less efficiently under oxygen limitation. The sudden stressful change in oxygen availability influenced significantly the starvation survival of cells from both growth rates (Table 1).…”
Section: Starvation Survivalsupporting
confidence: 92%
See 3 more Smart Citations
“…2). These results confirmed previous findings (CACCIARI et al 1985) and indicated that the organism grew less efficiently under oxygen limitation. The sudden stressful change in oxygen availability influenced significantly the starvation survival of cells from both growth rates (Table 1).…”
Section: Starvation Survivalsupporting
confidence: 92%
“…The loss of viability during starvation was an exponential process and its specific rate was reported as death rate that was calculated according to CHAMBERLIN and MITCHELL (1978). The rates of death (Table 1) were higher within the range of dilution rates in which morphological and physiological changes have been previously observed in the culture grown under the same nutritional conditions (CACCIARI et al 1983). …”
Section: Starvation Survivalsupporting
confidence: 58%
See 2 more Smart Citations
“…26,27]. It is noteworthy that a drop in ATP levels of Arthrobacter fluorescens was observed in the range of nutrients in which a decrease in respiratory activity was monitored [28]. Gustafsson [29] also reported a marked correlation between the ATP content and the specific heat production for Debaryomyces hansenii.…”
Section: The Use Of a Tp As A Chemical Signaturementioning
confidence: 99%